Off the grid [large type] - Tracy, P. J. (Tracy, P. J. Monkeewrench novel, 2012)
On a sailboat ten miles off the Florida coast, Grace MacBride, partner in Monkeewrench Software, thwarts an assassination attempt on retired FBI agent John Smith. A few hours later, in Minneapolis, a fifteen-year-old girl is discovered in a vacant lot, her throat slashed. Later that day, two young men are found in their home a few blocks away, killed execution-style. The next morning, the dead bodies of three more men turn up, savagely murdered in the same neighborhood. As Minneapolis homicide detectives Leo Magozzi and Gino Rolseth struggle to link the three crimes, they learn that there have been similar murders in other cities around the United States. Piece by piece, evidence accumulates, pointing to a suspect that shocks them to the core, uncovering a motive that puts the entire Midwest on high alert and Monkeewrench in the direct line of fire. Before it's all over, Grace and her partners, Annie, Roadrunner, and Harley Davidson, find themselves in the middle of a shocking collision of violence on a remote northern Minnesota reservation, fighting for their lives.